PROBLEMATIKA PEMBELAJARAN TAHFIDZ AL-QUR’AN PADA MASA PANDEMI COVID-19 DI SMP MUHAMMADIYAH 9 GEMOLONG SRAGEN - Dika Ayu Pradana; Nurul Latifatul Inayati (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2021)
The Covid-19 virus has a very big influence, one of which is in the world of education. No exception in learning Tahfidz Al-Qur'an. This study aims to identify the problems of learning Tahfidz al-Qur'an during the Covid-19 pandemic at SMP Muhammadiyah 9 Gemolong Sragen and the efforts made to overcome these problems. From the data collected, it was concluded that the existence of Covid-19 resulted in the learning of Tahfidz Al-Quran at SMP Muhammadiyah 9 Gemolong Sragen having several problems experienced by both teachers and students. The problems experienced by students include: a) Signals that are less supportive. b) Do not have a mobile phone or mobile phone is used by parents. c) Enthusiasm in memorizing is reduced. d) Late depositing memorization. e) The condition of the learning environment is not conducive. f) Do not have internet quota. The problems experienced by teachers include: a) The internet network is less supportive. b) Difficulty in assessing student memorization. c) Cannot accompany students directly. And the efforts made to overcome these problems include: a) Looking for a place where the signal supports it. b) Borrowing a relative's cell phone or joining a classmate during learning activities or may deposit memorization when the cellphone is not used by the parents. c) Teachers must improve their competence to encourage students to be more enthusiastic in memorizing the Qur'an. d) The teacher contacts the students or parents of students. e) The teacher allows students to be late in depositing rote until conditions are truly conducive. f) Students are encouraged to come to school and use the school's wifi in order to participate in teaching and learning activities. However, now students get quota assistance from the school. The efforts made to overcome the problems experienced by teachers: a) The teacher asks students to prepare memorizing the Al-Qur'an until the teacher can send Tahfidz Al-Qur'an learning materials. b) Contacting the parents of students to take part in Tahfidz Al-Qur'an learning and sending a rote deposit assignment. c) Using the WhatsApp application in carrying out Tahfidz Al-Qur'an learning and students depositing the memorization of the Qur'an via voice notes.